Evaluate the Elements That Contribute to the Success of Kaizen Implementation in Manufacturing Sector - Mohamad Ishak, Mohd Mokti (2012)
This study aims to investigate the relationship between worker attitude, skill, knowledge, and management support and success of kaizen implementation among SRM employees in the manufacturing sector. The relationship between those variables are predicted based on relevant literature, and are tested using survey results from 206 of the SRM employees in Arau, Perlis. Descriptive statistics analysis and inferential statistical analysis are used to analyze the corresponding characteristics of the sample. Reliability of measures is established by testing for both consistency and stability. Pearson’s Correlation are used to test the relationships between attitude and success of kaizen implementation, skill and success of kaizen implementation, knowledge and success of kaizen implementation, and management support and success of kaizen implementation. Overall results indicated that all the independent variables i.e. attitude, skills, knowledge and management support were significant influence to the success of kaizen implementation. Hypothesis one is accepted: There were positive relationships between attitude and success of kaizen implementation. Hypothesis two is accepted: There were positive relationships between skills and success of kaizen implementation. Hypothesis three is accepted: There were positive relationships between knowledge and success of kaizen implementation. Hypothesis four is accepted: There were positive relationships between management support and success of kaizen implementation. Attitude has strong influence contribute to the success of kaizen implementation. Skills and knowledge has moderate influence. However management support has less influence contribute to the success of kaizen implementation.